Penggunaan Media Belajar Miniatur Kasir dalam Meningkatkan Pemahaman Berniaga Siswa ABK di Sekolah Alam Le Cendekia - Wilda Ansar; A. Anifah Nutqhi Syam; A. Mutmainnah Syam; Rahmat (Journal of Research and Publication Innovation, 2023)
The aim of miniature cashiers as learning media for students with special needs is a way of learning that requires children to do direct training or practice. Miniature cashiers designed in such a way can help students with special needs train students in commerce and help them improve their ability to count and know the rupiah currency well. The method used in this study is a method with a qualitative approach that is descriptive. Data collection was carried out using observation techniques. The research was conducted on four students with special needs who attended Le Cendekia Boarding School from 15 till 18 May 2023. The use of learning media for miniature cashiers was considered quite effective in buying and selling simulations carried out with students with special needs. The results of this study are expected to be able to contribute to efforts to increase the understanding of commerce of students with special needs in three aspects observed in the study, namely recording products sold, knowledge of the total selling price, and accuracy in giving returns.